2010
DOI: 10.1590/s1980-57642010dn40300194
|View full text |Cite
|
Sign up to set email alerts
|

The generation of visual inferences in normal elderly Influence of schooling and visual complexity

Abstract: The generation of inferences makes the construction and comprehension of discourse easier, and integrates representations which add coherence to the arguments. Visuoperceptual and inferential deficits merge in the attempt to explain the difficulties that some individuals have in the comprehension of certain kinds of visual stimuli.Objectivesa) To examine the performance of cognitively healthy elderly subjects in the execution of visual inferences using pictures of different levels of complexity;b) To compare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Several studies have shown an association of the execution or reproduction of mental and memory tasks with schooling level. 11 - 16 The process of visual reproduction of a picture after a time interval, such as that used in the present study, is dependent on memory, especially short-term memory. 16 Moreover, the relationship between schooling and visual acquisition may influence the reliability of reproduction.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several studies have shown an association of the execution or reproduction of mental and memory tasks with schooling level. 11 - 16 The process of visual reproduction of a picture after a time interval, such as that used in the present study, is dependent on memory, especially short-term memory. 16 Moreover, the relationship between schooling and visual acquisition may influence the reliability of reproduction.…”
Section: Discussionmentioning
confidence: 95%
“… 11 - 16 The process of visual reproduction of a picture after a time interval, such as that used in the present study, is dependent on memory, especially short-term memory. 16 Moreover, the relationship between schooling and visual acquisition may influence the reliability of reproduction. 17 - 19 Our results show that individuals with over 8 years of schooling had superior performance to the other groups on visual reproduction of Pictures one and two ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 95%
“…Educational level is a highly recognized factor impacting cognitive performance, especially as measured by neuropsychological tests, which rely at a great extent on metacognitive processes highly dependent on formal training (as provided by schooling; Hamel & Joanette, 2007;Myers & Brookshire, 1996;Ribeiro, Freitas, Radanovic, & Mansur, 2010).…”
Section: Impairment Of Inferential Abilitiesmentioning
confidence: 99%
“…However, they used auditory stimuli as the assessment instrument. In Brazil, Ribeiro et al 16 investigated the performance of normal elderly on tasks of visual inference using pictures of different degrees of visual complexity and compared the performance of subjects according to schooling level. The results indicated that highly educated subjects maintained the same effectiveness in making inferences, independently of picture complexity, but visual complexity interfered with the low and medium educated subjects' ability to make inferences.…”
Section: Introductionmentioning
confidence: 99%